DEVELOPMENT OF STUDENT WORKSHEETS CLASS VIII SCIENCE LESSONS ON VIBRATION MATERIAL - Ai Rohaeti; Nur Hayati (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2022)
Science learning, which relies on K-13 and teachers, is a requirement for student abilities that include cognitive, affective, and psychomotor as targets for achieving graduation abilities. Limitations in communication and other learning support are not overall needs become obstacles in student learning activities, so learning can not form optimally. Achieve maximum learning teaching materials are needed that are proportional to the needs as a learning guide for students. A Student worksheet is a teaching material that contains a summary of the material, practice questions, and some work procedures. The purpose of this development research is to describe the LKPD development process in the science subject matter of Vibration and to explain the development output after the validation process. The ADDIE model that has five complex hierarchies is the development technique chosen in this development research. Research carried out resulted in a product in the form of LKPD for the science subject of vibration material at the SMP/MTs level of class VIII that was valid with a validity percentage of 87.19%. The development process is according to the stages under the ADDIE development model output is the development product validated by three validators, namely material experts, media, and science teachers.